Larger Pore Size Hollow Fiber Membranes as a Solution to the Product Retention Issue in Filtration‐Based Perfusion Bioreactors. Issue 2 (13th December 2018) - Wang, Samantha B.; Godfrey, Scott; Radoniqi, Flaka; Lin, Henry; Coffman, Jon
Abstract : Tangential flow filtration (TFF) and alternating tangential flow (ATF) filtration technologies using hollow fiber membranes are commonly utilized in perfusion cell culture for the production of monoclonal antibodies; however, product retention remains a known and common problem with these systems. To address this issue, commercially available hollow fibers ranging from several hundred kilo‐Daltons (kDa) to 0.65 μm in nominal pore size are tested and are all demonstrated to undergo moderate to severe product retention. Further investigation revealed accumulation of particles in the same size range (≈20–200 nm) as the pores. Based on the assumption that these particles contribute to product retention and membrane plugging, a hollow fiber with an unconventionally larger pore size is subsequently identified and demonstrated to drastically reduce product retention with no impact to cell clarification. Furthermore, these hollow fibers demonstrate surprisingly high membrane capacities, making them an attractive solution to the problem of product retention in perfusion reactors. Abstract : Biotechnology drugs are increasingly being made in perfusion bioreactors. These bioreactors suffer from poor product recovery as the material is harvested through the cell retaining tangential flow filtration membranes. Large pore membranes allow nearly 100% recovery of the product.